Interview with Walter Mignolo on "The geopolitics of knowledge in relation to Latin America" - Walsh, Catherine (2016)
Walter D. Mignolo is a professor and director of the Center for Global Studies and Humanities at Duke University in the USA. His most recent publications include; Local histories / global designs: coloniality, subaltern knowledges and border thinking (2000), The darker side of the renaissance: literacy, territoriality and colonization (1995) and "The many faces of cosmo-polis: critical cosmopolitanism and border thinking", in Public culture (12 / 3,2000). He is also a compiler and contributor of the volume Capitalism and Geopolitics of Knowledge: The Philosophy of Liberation in Contemporary Intellectual Debate, published by Ediciones del Signo, Buenos Aires, 2001